The impact of financial development and macroeconomics variables on economic growth - Noorhamizah, Abdul Wahab (2017)
Financial development is an important element for an effective and efficient financial sector which assisted in encouraging the economic growth in ensuring the flows of capital are channelled towards the most productive use, minimizing market frictions and reducing transactions costs. The development of financial sectors as a main indicator for the country’s economic growth is strongly recognized in the neo-classical views theory. The objective of the study is to determine the impact of financial development (domestic credit to private sector and gross domestic savings) and macroeconomics variables (inflation, real interest rate and trade) on economic growth for 47 of Asian countries. This study employs the unbalanced panel data in 47 of Asian countries for the period of 2000 and 2016. The dependent variable for this study is economic growth and the independent variables consist of domestic credit to private sector, gross domestic savings, inflation, real interest rate and trade. The study discovers the positive relationship between financial development and economic growth. In contrary, the study finds the negative relationship between two macroeconomics variables (inflation and real interest rate) and the economic growth. In addition, the results argue that trade is not the factor that influencing the economic growth. The findings of the study could assist the policy makers for the future policy making efforts.